2012
DOI: 10.1088/0004-637x/750/2/88
|View full text |Cite
|
Sign up to set email alerts
|

REVISITING THE LONG/SOFT-SHORT/HARD CLASSIFICATION OF GAMMA-RAY BURSTS IN THEFERMIERA

Abstract: We perform a statistical analysis of the temporal and spectral properties of the latest Fermi gamma-ray bursts (GRBs) to revisit the classification of GRBs. We find that the bimodalities of duration and the energy ratio (E peak /Fluence) and the anti-correlation between spectral hardness (hardness ratio (HR), peak energy and spectral index) and duration (T 90 ) support the long/soft − short/hard classification scheme for Fermi GRBs. The HR − T 90 anti-correlation strongly depends upon the spectral shape of GRB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 65 publications
5
97
1
Order By: Relevance
“…Most remarkable is that this model gives the theoretical explanation for the fulfillment of the E p,i -E iso relation for the short bursts (see Fig. 8 and Zhang et al 2012;Calderone et al 2015;Ruffini et al 2015b).…”
Section: Theoretical Interpretation Of S-grbs Within the Ns-ns Mergermentioning
confidence: 61%
See 1 more Smart Citation
“…Most remarkable is that this model gives the theoretical explanation for the fulfillment of the E p,i -E iso relation for the short bursts (see Fig. 8 and Zhang et al 2012;Calderone et al 2015;Ruffini et al 2015b).…”
Section: Theoretical Interpretation Of S-grbs Within the Ns-ns Mergermentioning
confidence: 61%
“…8 and Zhang et al 2012;Muccino et al 2013;Calderone et al 2015;Ruffini et al 2015b) and increase monotonically with E iso .…”
Section: General Propertiesmentioning
confidence: 83%
“…The Amati correlation was investigated (Basak & Rao 2013;Gruber 2012) and a link between short and long GRBs was discovered (Muccino et al 2013). It gave insight into the GRB afterglow population (Racusin et al 2011), allowed to observe a number of high-energy GRBs (with photon energies exceeding 100 MeV, or even 10 GeV) (Atwood et al 2013), and provided a verification of the short-long classification (Zhang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The division line between the long-duration GRBs (LGRBs) and short-duration GRBs (SGRBs) is around 2 seconds in the BATSE 50 − 300 keV band. Although the significance of this bimodality and the division line depend on the sensitivity and energy band of the detectors (Richardson et al 1996;Bissaldi et al 2011;Zhang et al 2012;Qin et al 2013), the authenticity of the bimodal T 90 distribution is confirmed not only with a larger BATSE sample (Meegan et al 1996;Paciesas et al 1999), but also by GRB data collected from other instruments such as BeppoSAX ), INTEGRAL Savchenko et al 2012;Bošnjak et al 2014), Swift and Fermi (Paciesas et al 2012;von Kienlin et al 2014). The existence of two phenomenological classes of GRBs is firmly established.…”
Section: Introductionmentioning
confidence: 97%